Implementation Of Jigsaw Coopertaive Learning And Gallery Walk Based On Practices To Develop Science Process Skills And Sscientific Attitude Of Students - Fitri Laila; Prasetyorini Prasetyorini; Kurniasih Kurniasih (JSEP (Journal of Science Education and Practice), 2021)
This study aims to obtain information on improving students ' science process skills and scientific attitudes through practical - based Jigsaw and Gallery Walk learning on the material organization of life. This research method uses a quasi-experimental design with a two-experimental pre-posttest group design, where no one acts as a control group, both groups act as an experimental group that is given different treatment and both are given pretest and posttest. The object of this research is the students of class VII.1 and VII.2 with 41 students each. The instruments used are in the form of multiple choice test questions, KPS observation sheets or performance assessments and questionnaires for scientific attitudes before and after learning which are equipped with learning implementation observation sheets and student and teacher questionnaires. The results of this study indicate that: (1) there are differences in the KPS of students who carry out practicum-based Jigsaw and Gallery Walk learning. (2) there are differences in the scientific attitude of students who carry out practical-based Jigsaw and Gallery Walk learning. (3) practicum-based Jigsaw and Gallery Walk learning can develop students' KPS and Scientific Attitudes. Based on the normalized gain scores, these two learnings have moderate values, both on the KPS and students' scientific attitudes. Thus, it can be concluded that Jigsaw and Gallery Walk learning can improve students' KPS and Scientific Attitudes.